STUDIES ON EFFECT OF COW DUNG ASH IN AQUEOUS MEDIUM AS FOLIAR SPRAY ON Zea mays (POACEAE) - A. P. PATIL,; S. P. DORUGADE,; S. V. MADHALE,; A. S. DIVE,; P. D. SHIRGAVE, (The Bioscan, 2023)
Present work deals with study on effect of cow dung ash in aqueous medium as foliar spray on commercial crop and experimental crop plant Zea mays (Poaceae). We discovered that using cow dung ash as a foliar spray in an aqueous medium improves plant development. In comparison to 1% to 3% and 6% to 10%, the 4% and 5% cow dung ash sprouts are more successful, exhibiting robust development, dark green colored leaves, and pest-free healthy plants. Cow dung ash sprouts between 1% and 3% demonstrate a steady rise in plant height and color. While 6% to 10% of the ash from cow manure is less effective or withering.